仿生四足机器人的设计与实现 - 宫赤坤; 吴启利; 谷根 (Jixie chuandong)
Through studying the four-legged animal’s walking style,the bionic quadruped robot is designed.Jacobi matrix and the kinematics principle are obtained by analyzing its mechanical structure using DH method.The continuity of quadruped gait is designed and the model with constraints is verified in ADAMS.Through the analysis of the displacement of the center of mass and joint torque,the rationality of the gait programming and selected motor meets the requirement.